Aggressive angiomyxoma - Devi, T. Ramani; Sangavi, D.; Deepika, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Angiomyxoma is a rare slow-growing, benign low-grade tumor occurring in women of reproductive age group which is known for its recurrence. The symptoms are variable. Mrs. K. aged 33 years, reached our outpatient department (OPD) with complaints of painless swelling on the right labial region which she was feeling uncomfortable while sitting. Mass was found to be mobile with no evidence of inflammatory change. The location of the mass made us think about, Bartholin’s cyst and hence surgical excision of the mass was done. The whole mass was found to be lying below the fat in the right labial region and wide excision was completed. The histopathology of the mass was reported as angiomyxoma. Angiomyxoma arises from the mesenchymal tissue and it is locally invasive with high recurrence rate. It is more common in females. Mostly seen in the vulvovaginal, pelvic cavity and perineum. The lesion can reach huge size. It has to be differentiated from gynecologic malignancies, cyst, abscess and hernia. Histology along with immune-histochemistry can confirm the lesion. Wide excision is the mode of treatment. Incomplete excision can lead to relapse. Relapse can happen in 35-72% of the cases. Local recurrence may occur between 2 months to 15 years following initial diagnosis. Hence, follow up is essential. Angiomyxoma is a very rare condition and only around 250 cases have been reported in the world literature. It has to be differentiated from other benign conditions. Diagnosed by non-invasive techniques like ultrasound sonography (USG), magnetic resonance imaging (MRI) and computed tomography (CT). Wide excision is the treatment of choice. Long term follow up is needed as recurrences are high.